Is hybrid coronary revascularization really beneficial in the long term?. (21st June 2021) - Wang, Chuan; Li, Ping; Zhang, Fan; Li, Jingxing; Kong, Qingyu
Abstract:  : OBJECTIVES: This analysis aimed to compare both short- and long-term outcomes of hybrid coronary revascularization (HCR) with different techniques and coronary artery bypass grafting (CABG). METHODS: Twenty-three studies were included, covering 10 468 different patients, among whom 2403 patients underwent HCR with either simultaneous or staged method and 8065 patients underwent CABG. RESULTS: Compared with CABG, HCR had a statistically significant lower risk of stroke [odds ratio (OR) = 0.55, P  = 0.049], major adverse cardiac and cerebrovascular events (OR = 0.69, P  = 0.024) and blood transfusion (BT) (OR = 0.39, P  < 0.001), whereas no significant differences were detected in mortality, myocardial infarction and repeat revascularization. A network meta-analysis showed that simultaneous HCR had significantly better outcomes in stroke (OR = 0.24, P  = 0.01) and major adverse cardiac and cerebrovascular events (OR = 0.29, P  < 0.001), and staged HCR had a significantly better outcome in BT (OR = 0.31, P  < 0.001). According to the frequentist statistic results, simultaneous HCR had the highest probability of being the best treatment in terms of mortality (84%), stroke (97%), myocardial infarction (88%) and major adverse cardiac and cerebrovascular events (99%), whereas staged HCR had the highest probability of being the best in postoperative repeat revascularization (59%) and BT (83%). However, long-term results showed no significant difference between the HCR and CABG techniques. CONCLUSIONS: HCR appears to be a feasible option for multivessel coronary artery disease patients. Compared to traditional CABG, HCR had lower risk of adverse events in the short term, but in the long term, survival rate and freedom from major adverse cardiac and cerebrovascular events rate were similar between groups.